Large-Scale Containment Cooler Performance Experiments under Accident Conditions - Ralf Kapulla; Guillaume Mignot; Domenico Paladino (Science and Technology of Nuclear Installations)
Computational Fluid Dynamics codes are increasingly used to simulate containment conditions after various transient accident scenarios. This paper presents validation experiments, conducted in the frame of the OECD/SETH-2 project. These experiments address the combined effects of mass sources and heat sinks related to gas mixing and hydrogen transport within containment compartments. A wall jet interacts with an operating containment cooler located in the middle (M-configuration) and the top (T-configuration) of the containment vessel. The experiments are characterized by a 3-phase injection scenario. In Phase I, pure steam is injected, while in Phase II, a helium-steam mixture is injected. Finally, in Phase III, pure steam is injected again. Results for the M-configuration show helium stratification build up during Phase II. During Phase III, a positively buoyant plume emerging from the cooler housing becomes negatively buoyant once it reaches the helium-steam layer and continuously erodes the layer. For the M-configuration, a strong degradation of the cooler performance was observed during the injection of the helium/steam mixture (Phase II). For the T-configuration, we observe a mainly downwards acting cooler resulting in a combination of forced and natural convection flow patterns. The cooler performance degradation was much weaker compared with the M-configuration and a good mixing was ensured by the operation of the cooler.